Unmanned aerial vehicles in civilian logistics and supply chain management - Kille, Tarryn, 1979-; Bates, Paul R., 1959-; Lee, Seung Yong, 1971- (Business Science Reference, 2019)
"This book investigates the opportunities and challenges of the use of unmanned aerial vehicles in logistics and supply chain management. It also explores the operational and integration challenges associated with this emerging technology"--